Perceptions and livelihood uses of an invasive alien tree (acacia dealbata) by rural communities in the Eastern Cape - Agripa, Ngorima (Rhodes University, Faculty of Science, Department of Environmental Science, 2017)
The negative impacts which invasive alien species have on ecosystems are well documented but there is paucity of information on their impacts on rural communities. Due to ecological impacts that may be associated with Acacia dealbata invasions the Agricultural Research Council Plant Protection Institute is considering releasing a biocontrol agent for A. dealbata. The actual social impacts of A. dealbata invasion and control are likely to be related to its importance in rural livelihoods. This thesis reports on the perceptions and livelihood uses of A. dealbata in the Eastern Cape. Three study sites were assessed, Matatiele, Mount Fletcher and Maclear. The study involved 150 household surveys, one focus group discussion and one transect walk at each site, key informant interviews and frequent house visits to acquire reliable data. Results show that 100 % of households in the three sites use Silver Wattle extensively for firewood. In Matatiele 64 %, 72 % in Mount Fletcher and 84 % of households in Maclear use Silver Wattle for fencing. To carve tools 76 % in Matatiele, 76 % in Mount Fletcher and 84 % households in Maclear use Silver Wattle. For medicinal purposes 18 % in Matatiele, 20 % in Mount Fletcher and 16 % in Maclear use Silver Wattle, whilst 78 % in Matatiele, 80 % in Mount Fletcher and 80 % in Maclear use it for fodder purposes. Many respondents felt that Silver Wattle is too abundant within their areas such that it now has many negative impacts associated with it. Perceptions of local people towards A. dealbata are neither static nor uniform, but are influenced by time since the invasion and now abundance of the species. There are no alternatives which provide the same services provided by Silver Wattle. Benefits and constraints due to A. dealbata invasion are experienced by everyone irrespective of wealth and gender. In conclusion, Silver Wattle is a valuable resource to these rural communities, but increasing abundance is incurring high costs to grazing resources and landscape accessibility.
Keywords: Uncatalogued